Políticas públicas para a agricultura familiar no município de Entre Rios do Oeste: uma análise a partir da teoria ator orientado - Besen, Fabíola Graciele (2016)
The demographic changes that have taken place and are underway in Brazil, both in its growth and in the mobility of the population from rural to urban, have attracted attention from public managers only since the 1990s. Public policies for agriculture are still in the process of being understood And incorporation either by the public authorities or by the producers because they do not have access, knowledge or interest in them. Given this scenario, the general objective of this work is to analyze the public policies made available to the family farmer, their effectiveness aiming at the permanence of the man in the field. To this end, the study was conducted in the municipality of Entre Rios do Oeste during the period 2013/2016 and an appreciation of the public policies offered by the municipality and how family farmers are beneficiaries of these policies. The study focused on the following research problem: Are the public policies aimed at family agriculture in the municipality of Entre Rios do Oeste contributing to the development of the farmers (beneficiary actors), maintaining their fixation in the rural area with income diversification for the promoted actions? The study was carried out with agroecological family farmers associated to APOER - Association of Organic Producers of Entre Rios do Oeste. As a theoretical basis, Norman Long's Theory-Oriented Theory was used to verify how the family agriculture represented by organic farmers work and operationalize their objectives and practices of agricultural management with the municipality for the construction of public policies that contribute to its maintenance in the field . The research is classified as bibliographic, descriptive and exploratory regarding the objectives, with quantitative and qualitative approach and the techniques used are documental analysis and semi structured interview. This work, with the adopted procedures, indicates the actions developed by the public power to attend the family agriculture units, through its public policies, with the interaction of the involved actors and technical criteria aiming at setting the producers in the field and with adequate conditions of Life and income. It is concluded that public policies should not be projects with limits in space and time, but must be built by all agents considering the strategies, practices and motivations of local actors to achieve the expected results.